VISUAL ANALYSIS OF THE CAPITAL CITIES OF DEVELOPED COUNTRIES' PORTALS (Proceeding of the International Conference on Arts and Humanities, 2019)
The rapid growth of information and communication technology has led to dramatic changes in people's daily lives. This revolution has resulted in a new form of government, known as e-government. The effective use of e-government in municipalities is referred to as municipal e-government. The main purpose of this research is to extract the visual features which have been used in municipality portal graphic design. This study is mixed methods research; the results of the research have been reached through simultaneous analysis of qualitative and quantitative approaches. The population of this study is all images of the urban portals of all capitals in developed countries. Sample includes portals of the capital cities in the four English-speaking countries, which are also among the top 10 in the 2015 ranking of e-government ranking. A total of 50 samples were selected from four cities. The samples have been examined using a researcher-made checklist whose validity and reliability have been provided by pre-test and re-test. The visual elements in the samples are evaluated with the checklist. Analysis of the research data has been carried out as quasi-quantitative. According to the results, there are many similarities in the design of graphical user interface. However, there are differences.
Keywords: e-government; portal; graphical user interface; graphic design